2020
DOI: 10.1152/ajprenal.00429.2020
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the CDKL5-SOX9 signaling axis in rhabdomyolysis-associated acute kidney injury

Abstract: Acute kidney injury (AKI) is a common clinical syndrome associated with adverse short and long-term sequelae. Renal tubular epithelial cell (RTECs) dysfunction and cell death are among the key pathological features of AKI. Diverse systemic and localized stress conditions such as sepsis, rhabdomyolysis, cardiac surgery, and nephrotoxic drugs can trigger RTEC dysfunction. Through an unbiased RNAi screen, we recently identified cyclin-dependent kinase-like 5 (Cdkl5) also known as serine/threonine kinase 9 as a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…These genes are notable in that they have been shown to regulate several prosurvival pathways on nonrenal epithelia. Furthermore, they showed that this prosurvival, Sox-9-dependent transcriptional signature was activated and inhibited, respectively, in the kidneys of PTEC-specific Cdkl5 and Sox9-null mice after IRI-, cisplatin-, and rhabdomyolysis-induced AKI (5,6). These findings are consistent with the authors' conclusion that Sox9 acts downstream of Cdkl5 to mediate the cytoprotective effects of Cdkl5 inhibition after AKI.…”
Section: The Cdkl5-sox9 Regulatory Axis In Akisupporting
confidence: 77%
See 4 more Smart Citations
“…These genes are notable in that they have been shown to regulate several prosurvival pathways on nonrenal epithelia. Furthermore, they showed that this prosurvival, Sox-9-dependent transcriptional signature was activated and inhibited, respectively, in the kidneys of PTEC-specific Cdkl5 and Sox9-null mice after IRI-, cisplatin-, and rhabdomyolysis-induced AKI (5,6). These findings are consistent with the authors' conclusion that Sox9 acts downstream of Cdkl5 to mediate the cytoprotective effects of Cdkl5 inhibition after AKI.…”
Section: The Cdkl5-sox9 Regulatory Axis In Akisupporting
confidence: 77%
“…Certainly, the two papers from the Pabla laboratory provide strong genetic and pharmacological data that Cdkl5 is a druggable candidate target for therapeutic intervention in AKI. The fact that this has been shown in at least three different models of AKI (5,6), and that there is genetic evidence that CDKL5 gene polymorphisms are risk factors for CKD progression (4), suggest that CDKL5 is likely to be involved in the heterogeneous pathobiology of injury in patients with AKI. However, in my opinion, a number of important questions remain to be answered before these findings are translated from the bench to the bedside:…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations